Free Convection MHD Flow with Thermal Radiation from an Impulsively-Started Vertical Plate - G. Palani; I. A. Abbas (Nonlinear Analysis, 2009)
This paper investigates the combined effects of magnetohydrodynamics and radiation on free convection flow past an impulsively started isothermal vertical plate with Rosseland diffusion approximation. The fluid considered is a gray, absorbingemitting radiation but a non-scattering medium, with approximate transformations the boundary layer governing the flow are reduced to non-dimensional equations valid in the free convection regime. The dimensionless governing equations are solved by the finite element method.